Analysis of Micro Financing Product Development at BSI KCP Stabat - Ahmad Firdaus Lingga; Sugianto; Tuti Anggraini (Al-Kharaj: Journal of Islamic Economic and Business, 2026)
This study aims to analyze first, BSI's microfinance products, second, the obstacles and challenges of marketing BSI's microfinance products, and third, the strategy and process of developing BSI microfinance products. The research method used is a qualitative descriptive approach with data collection through observation, interviews, documentation and surveys to customers and related parties of one of BSI's branch offices. The results of the study show that BSI's microfinance products, such as KUR Super Micro, KUR Micro, and non-KUR products, are designed according to sharia principles with an easy application process and supported by service digitization. This product has a significant positive impact on increasing capital, production capacity, income, and welfare of MSME actors. However, product development still faces obstacles such as low Islamic financial literacy, complex administrative requirements, high micro business risks, and limited access in remote areas. The market opportunity for sharia microfinance is very large considering the large MSME segment and the support of government regulations. Therefore, effective development strategies include product innovation, increasing financial literacy, using digital technology, strengthening partnerships, and improving human resource competence